Prevalence and Risk Factors of Asthma, Wheezing, and Allergic Rhinitis in Asian Children: A Systematic Review - Priyanka I Dhumal; Sammita J Jadhav (Indian Journal of Respiratory Care)
Background: There is limited information on the impact of risk factors on respiratory diseases among children in the Asian region. Hence, the aim of the study is to find the prevalence of asthma, wheezing, and allergic rhinitis (AR) in Asian children and identify the contributing factors to the development of respiratory diseases among children in Asian continents. Investigating these exposures is essential to mitigate onset and enhance pulmonary health. Methods: A total of 5,942 articles were collected from three databases: Medline, Web of Science, and Scopus. We included only English articles published in Asian countries in the last 5 years (2019–2024). Review articles were excluded, and only cohort, cross-sectional, and case-control studies for asthma, wheezing, and AR were selected. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were followed for the extraction of studies. Results: AR was the most prevalent among the three respiratory diseases examined from 52 studies across 12 Asian countries. Asthma prevalence ranged from 2 to 29.4%, wheezing from 6 to 27%, and AR from 2 to 33%. The associations may be linked to the local contexts, such as pollution reduction and school-based interventions. About 40% of the studies indicated the effect of child-related and environmental factors, while 23% emphasized maternal factors. Conclusion: Understanding the maternal, environmental, and child's lifestyle factors allows public health initiatives to reduce exposure and minimize the adverse effects on respiratory health. Children at risk can improve their health status through early identification of risk factors.